2015
DOI: 10.1155/2015/903478
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Temperature Sodium Hydroxide Immersion on Fusion Bond Epoxy Coating

Abstract: Fusion Bond Epoxy (FBE) coating system was exposed to 5% sodium hydroxide at elevated temperature for 30 days. The result of exposure showed formation of adhere deposit layer, a discolored zone underneath and remaining un-affected bulk of the coating. The deterioration of the coating was characterized using analytical techniques like scanning electron microscopy (SEM), energy-dispersive X-ray (EDAX) spectroscopy, attenuated total reflection-Fourier transform infrared spectroscopy (ATR-FTIR), differential scann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Several works have shown that FBE could present failure when used at high temperature due to its sensibility to water transport to the interface [171][172][173]. It is not uncommon to have high service temperature in offshore applications.…”
Section: Performance Of Powder Coatingsmentioning
confidence: 99%
“…Several works have shown that FBE could present failure when used at high temperature due to its sensibility to water transport to the interface [171][172][173]. It is not uncommon to have high service temperature in offshore applications.…”
Section: Performance Of Powder Coatingsmentioning
confidence: 99%
“…However, the Rp value decreased for P4 (in which the henna percentage was 12%) to the value of 6252.8 kΩ. The formation of a deposited layer on the substrate led to the production of a high impedance value of the coating and slowed down the rate of electrolyte penetration into the coating [25]. Figure 3 shows thermography of coated aluminium with different percentages of henna extract.…”
Section: Electrochemical Studymentioning
confidence: 99%
“…It indicates that when a percentage of henna extracts increase, the corrosion resistance also increases and the corrosion rate decreases. Furthermore, the high impedance value of the coating is related to the formation of the deposited layer and consequently slows down the rate of electrolyte penetration into the coating [15]. Figure 7 shows the plot of stress and strain curve.…”
Section: Electrochemical Impedance Spectroscopy (Eis)mentioning
confidence: 99%